2017
DOI: 10.2967/jnumed.117.191197
|View full text |Cite|
|
Sign up to set email alerts
|

68Ga-DOTATOC Imaging of Neuroendocrine Tumors: A Systematic Review and Metaanalysis

Abstract: Ga-DOTATOC, a somatostatin receptor-targeted ligand, has been used clinically in Europe over the past decade for imaging neuroendocrine tumors (NETs). It appears to be quite sensitive and effective for clinical management decision making. This metaanalysis summarizes the efficacy of Ga-DOTATOC for several distinct indications and is intended to support approval of this agent by the U.S. Food and Drug Administration. The major electronic medical databases were searched for relevant papers over the period from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 31 publications
0
85
0
2
Order By: Relevance
“…18 F‐FDOPA PET/CT performed better than SRS and CT of midgut NETs but may have suboptimal sensitivity in some pancreatic NETs . Several studies have shown that 68 Ga‐DOTA‐SSAs like 68 Ga‐DOTATATE, 68 Ga‐DOTATOC and 68 Ga‐DOTANOC have a high detection rate and a high impact on patient management, especially in NETs with unknown primary or in potential candidates for curative surgery or requiring liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…18 F‐FDOPA PET/CT performed better than SRS and CT of midgut NETs but may have suboptimal sensitivity in some pancreatic NETs . Several studies have shown that 68 Ga‐DOTA‐SSAs like 68 Ga‐DOTATATE, 68 Ga‐DOTATOC and 68 Ga‐DOTANOC have a high detection rate and a high impact on patient management, especially in NETs with unknown primary or in potential candidates for curative surgery or requiring liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…68‐Gallium DOTATOC PET‐CT is also a powerful tool in the management of patients with NET, for evaluating the presence and extent of the disease and to assist in treatment decision‐making …”
Section: Discussionmentioning
confidence: 99%
“…This indication resulted in significant disagreement within the workgroup. On the one hand, the overall yield of finding a NET in this patient population is low, and SSTR PET may also result in false-positives that could lead to unnecessary additional tests or procedures (12). However, in such a situation, a negative SSTR PET result may play an important role, as it could end the diagnostic workup, resulting in a more cost-effective evaluation.…”
Section: Scenario 6: Monitoring Of Nets Seen Predominantly On Sstr Pementioning
confidence: 95%
“…No adverse events have been reported in association with the administration of SSTR PET agents (12).…”
Section: Safety and Dosimetry Of Sstr Petmentioning
confidence: 99%
See 1 more Smart Citation